Can the Childhood Physical Activity Questionnaire Be Used to Identify Physical Activity Levels in Children With Asthma? - Mattienne R. van der Kamp; Mattienne R. van der Kamp; Mattienne R. van der Kamp; Bram W. Nieuwdorp; Boony J. Thio; Monique Tabak; Monique Tabak; Arvid W. A. Kamps; Hermie J. Hermens; Hermie J. Hermens; Jean M. M. Driessen; Jean M. M. Driessen (Frontiers Media S.A., 2021)
Objective: Children with asthma who are physically active have a better quality of life, emphasizing the importance of activity monitoring and promotion in daily life. The validity of self-reported activity measurements has been questioned in pediatric populations. In this study, we aim to compare the Physical Activity Questionnaire for Children (PAQ-C) with objectively measured PA using accelerometry.Design: In this comparison study, the pooled dataset of two cross-sectional studies was used, which prospectively home-monitored PA using the alternative self-report PAQ-C questionnaire as well as with the criterion standard accelerometry (Actigraph wGT3X-BT and GT1M).Participants:Ninety children with pediatrician-diagnosed asthma participated in the study.Main Outcome Measures:Correlation coefficients were calculated to determine the relation between the PAQ-C and accelerometer data. The predictive value of the PAQ-C in differentiating between achieving and failing the recommended daily level of moderate-to-vigorous activity (MVPA) was evaluated with receiver operator characteristic (ROC) analysis.Results: The results showed weak to moderate correlations of the PAQ-C with the accelerometer data (r = 0.29-0.47). A PAQ-C cutoff of 3.09 showed the best performance on predicting whether the recommended level of MVPA was achieved. With this cutoff, 21 of the 39 children that did achieve their daily MVPA level (53.8% sensitivity) and 33 of the 46 children that did fail their daily MVPA level (71.7% specificity) were correctly classified. A PAQ-C score of 3.5 revealed a negative predictive value of 100% for assessing physical inactivity.Conclusion: This study revealed a weak relation between the PAQ-C and PA assessed with accelerometry. However, a PAQ-C score of 3.5 or higher might be used as a low-cost and easy-to-use PA screening tool for ruling out physical inactivity in a portion of the pediatric asthma population.Clinical Trial Registration: Netherlands Trial Register: Trial NL6087.